Chromosome-level changes and genome elimination by manipulation of CENH3 in carrot (Daucus carota) - Meyer, Chandler M.; Goldman, Irwin L.; Krysan, Patrick J. (Frontiers in Plant Science, 2023)
Hybrid cultivars are valuable in many crop species due to their high yield, uniformity, and other desirable traits. Doubled haploids, which have two identical sets of chromosomes, are valuable for hybrid breeding because they can be produced in one generation, in comparison to the multigenerational process typically used to produce inbred parents for hybrid production. One method to produce haploid plants is manipulation of centromeric histone H3 (CENH3). This method of producing haploids has so far been successful in Arabidopsis, maize (Zea mays), and wheat (Triticum aestivum). Here we describe modification of CENH3 in carrot (Daucus carota) to test for the ability of these modifications to induce uniparental genome elimination, which is the basis for haploid induction. Base editing was used to make cenh3 mutant plants with amino acid substitutions in the region of CENH3 encoding the histone fold domain. These cenh3 mutant plants were then outcrossed with CENH3 wild-type plants. Using PCR-based genotyping assays, we identified two candidates for genome elimination. One candidate was classified as a putative aneuploid plant in which chromosome 7 is in a single copy state. The other candidate was characterized as a putative tetraploid that was likely haploid during its genesis. Our results suggest that this putative tetraploid inherited all of its chromosomes from the CENH3 wild-type parent and that the genome of the cenh3 mutant plant was lost. This study provides evidence that modification of CENH3 in carrot has the potential to induce genome elimination and ploidy changes in carrot.